Market frictions, allocative efficiency and aggregate productivity in the manufacturing sector: evidence from Zimbabwe - Kamutando, Godfrey Paradzai (School of Economics, 2021)
Underdevelopment arises not only from the lack of production resources such as capital and labour but also as a consequence of the inefficient allocation of available resources. Reducing the misallocation of resources is, therefore, seen as one of the channels through which substantial increases in aggregate productivity and incomes of emerging economies can be achieved. This thesis analyses how market distortions contribute to the misallocation of resources within and between the formal and informal manufacturing sectors in Zimbabwe. The thesis is guided by three broad shortcomings in the available literature. First is the exclusion of the informal sector, a major source of economic activity in emerging economies, in the analysis of misallocation. Second is the paucity of studies that isolate the distinct factor market distortions that drive misallocation in emerging economies. Third, notwithstanding the importance of allocative efficiency in aiding aggregate TFP and the abundant informal sector activities in emerging economies, few studies have analysed misallocation in sub-Saharan Africa. A key reason for the above is the lack of detailed firm and employee data. The thesis is structured around three main research objectives. Firstly, it quantifies the extent of allocative inefficiency within and between the formal and informal manufacturing firms in Zimbabwe. Secondly, it investigates the extent to which financial access constraints contribute to misallocation and hinder firm performance. Finally, it tests for labour market segmentation within and between formal and informal manufacturing sectors as a source of labour misallocation. To conduct the analysis, the thesis draws on the recently available Matched EmployerEmployee manufacturing firm-level survey dataset for formal and informal sector firms and workers that was conducted between 2015 and 2018 as part of this thesis. These surveys provide unique data on firm production activities and on worker wages and characteristics that allow for the analysis of resource misallocation and its sources in Zimbabwe. The thesis comprises of three main chapters apart from the general introduction and conclusion chapters. Chapter 2 draws on the Hsieh & Klenow (2009) approach to measure the extent of allocative inefficiency within and between the formal and informal manufacturing sector firms in Zimbabwe. The results reveal a high degree of misallocation that is more pronounced in informal sector firms. Output and capital market distortions both contribute substantially to resource misallocation, but it is the capital distortions that are strikingly large for the informal sector firms. Further, there is a positive correlation between firm productivity and indicators of misallocation, implying that the more productive firms face relatively high distortions preventing them from growing to their optimal level, thus exacerbating aggregate TFP losses. Specifically, the results show that by removing misallocation of resources, aggregate TFP gains of 153.6 percent can be realised. Chapter 3 empirically tests how financial access constraints affect the efficient allocation of resources. The focus of this chapter is on informal firms, given the availability of data, and the presence of relatively high capital distortions that these firms are found to be facing. While the direct impact of financial access constraints on firm performance has been studied extensively, the indirect effect on aggregate productivity via the allocation of resources across firms has received less attention. This is important, as financial constraints can attenuate or exacerbate aggregate TFP losses through misallocation. The empirical analysis is conducted using two approaches. Firstly, regression analysis is used to assess the extent to which financial access constraints exacerbate or attenuate the misallocation effects arising from capital market distortions. Secondly, in order to explore the channels through which factor market distortions affect misallocation, productivity-enhancing re-allocation regressions (following Bartelsman et al., 2017) are estimated to test how initial financial access constraints faced by firms affect subsequent investment and employment growth. The analysis reveals a significant positive association between financial access constraints and indicators of misallocation, suggesting that financial access constraints are an important source of misallocation. Further, the interaction of financial constraints and firm productivity is positive, implying that these constraints amplify the aggregate TFP losses due to misallocation. Disaggregating the analysis further shows that financial access constraints affect misallocation through both capital and output distortions. Finally, the productivity-enhancing reallocation regressions indicate that financial access constraints affect firm investment negatively but are not significant in constraining employment growth. The findings indicate that the negative effects of financial access constraints on firm growth, allocative efficiency and hence aggregate TFP operate through the investment channel. Chapter 4 investigates the extent, type and sources of labour market segmentation within and between the formal and informal manufacturing sectors. The chapter exploits the panel dimension of the formal and informal worker surveys in the Matched Employer-Employee dataset. Wage differentials between labour market subgroups are used to test for the extent and types of segmentation. The rent-sharing model is then used to test for the importance of profitper-worker as a source of labour market segmentation. We find evidence of labour market segmentation between the regulated formal sector and the unregulated informal sector, with a conditional wage gap of 25 percent. The results also reveal segmentation between permanent and contract workers within the formal sector, but no evidence of wage differentials between contract and informal sector workers after controlling for human capital endowments. Further, a significant positive association between wages and profits-per-worker is estimated in the formal sector. The results suggest that labour markets are segmented due to rigidities in labour markets regulations and institutions that are associated with registered formal sector firms. Overall, the thesis underscores the importance of idiosyncratic distortions and factor market frictions, such as access to finance constraints and labour market regulations, as a source of inefficiencies and reductions in aggregate TFP. It shows that market distortions in Zimbabwe curtail the efficient allocation of production resources and constrain the performance of manufacturing sector firms, particularly in the informal sector. Thus, a policy framework that aims at reducing market frictions and distortions may substantially enhance allocative efficiency and firm performance, and through this, boost aggregate TFP.